Pelaksanaan Akreditasi Sekolah di SMKF Ikasari Pekanbaru - Eviati; Ghifari, Mahdini Al; Khafizin, Mohd.; Simbolon, Santi; Sohiron (Sekolah Tinggi Agama Islam Hasan Jufri Bawean, 2024)
This research aims to describe the implementation of school accreditation as an effort to ensure the quality of education at SMK Farmasi Ikasari Pekanbaru. The approach and method used in this research are descriptive qualitative, with data collected through interviews, observations, and document analysis. The data analysis technique employed is qualitative analysis, which includes data collection, data reduction, data presentation, and conclusion drawing. This study found that the process of preparing accreditation instruments at SMKF Ikasari Pekanbaru involves well-coordinated steps, including the preparation of forms in accordance with instruments provided by BAN S/M Province. The eight national education standards that are the focus of the accreditation instruments include aspects of content, learning processes, graduate competencies, educator qualifications, facilities and infrastructure, school management, financing, and educational assessment. The main supporting factor in this process is the implementation of a digital-based data system, which increases the efficiency of data collection, while the inhibiting factors include the technological experience gap among teachers and the implementation of accreditation during holidays. With high enthusiasm from the teachers and the collaborative efforts of the accreditation team, SMKF Ikasari Pekanbaru managed to overcome these challenges, ensuring that the accreditation requirements are met according to the set standards, thereby maintaining the school's reputation and future prospects